Language curriculum design - Nation, I. S. P. (Routledge, 2009)
Crystal-clear and comprehensive yet concise, this text describes the steps involved in the curriculum design process, elaborates and justifies these steps, and provides opportunities for practicing and applying them. The description of the steps is done at a general level so that they can be applied in a wide range of particular circumstances. The process comes to life through plentiful examples of actual applications of the steps. Each chapter includes: examples from the authors’ experience and from published research, tasks that encourage readers to relate the steps to their own experience, case studies and suggestions for further reading that put readers in touch with others’ experience.